Multinational corporate social responsibility, ethics, interactions and Third World governments: An agenda for the 1990s - Amba-Rao, Sita C. (Journal of business ethics, 1993)
A critical literature on mulitnational corporate social responsibility has developed in recent years. Many authors addressed the issue in the Third World countries. This paper reviews the literature, focusing on the relationship between the multinational corporations (MNCs) and Third World governments in fulfilling the social responsibility, based on the underlying ethical imperative., There is a growing consensus that both corporations and governments should accept moral responsibility for social welfare and individual interests in their economic transactions. A collaborative relationship is proposed where the MNCs share information based on global experiences and offer input into host government developmental policies, and aid their implementation. The government, in turn, provides a reasonable regulatory environment. This calls for ongoing interactions among officials at all levels of the two institutions, with the local corporate subsidiary playing a pivotal role. The desired conduct of the parties is reinforced by international organizations and other constituents, representing common human concerns across cultures. These relationships are examined and an agenda for policy and action by the MNCs and the Third World governments is developed., The accelerated growth in the number of multinational corporations (MNCs) and their worldwide scope, with concentration of economic and political power draws attention to corporate social responsibility. Furthermore, a meeting of the United Nations Conference on Trade and Development (UNCTAD) in 1987, with delegates from 141 developed and developing countries concluded with a major agreement.